Metaphors Expressing Emotions in Lisa Kleypas’s Rainshadow Road Novel - Ko, Novi Liana; Winiharti, Menik (Bina Nusantara University, 2014)
Metaphors have been always interesting to explore since they are able to represent many things, one of which is feelings. Article examined the metaphorical sentences which expressed emotions found in Lisa Kleypas’s the Rainshadow Road. Library research was conducted to find the kinds of emotions which were expressed by the metaphorical sentences. It was also done to figure out what the metaphors refered to. Another objective was to reveal the most dominant emotion which appeared through the metaphors expressed in the novel. The analysis used metaphor theory to compare the dictionary meaning and the metaphorical one. The result shows that there are various emotions which are expressed through the metaphorical sentences. Happiness is found as the most dominant emotion which appears in the novel.